The likelihood of sympatric speciation and morphological divergence in plants - Ingrid Olivares; Søren Faurby; Rodrigo Cámara-Leret; Alex L. Pigot (Proceedings of the National Academy of Sciences, 2025)
Sympatric speciation is considered rare, but oceanic Howea palms, crater lake cichlids, and parasitic indigobirds provide compelling evidence that it occurs. Still, the frequency of sympatric speciation and its relationship to morphological divergence in plants remains poorly understood, especially in plants. Here, we analyze the geographic distributions, traits, and divergence times of palm and conifer sister species (740 species from 108 genera) to determine the dominant geographic mode and role of morphological divergence in plant speciation. We show that allopatric speciation is dominant, and while frequent sympatric speciation cannot be discounted, the most likely scenario is that zero (conifers) or 10% (palms) of speciation events occur in sympatry. Our models show that the incidence of sympatry among sister pairs rises rapidly within the first million years after speciation and then declines, suggesting that species failing to attain sympatry early tend to remain allopatric. Finally, we find no evidence for morphological divergence in allopatric or sympatric palms. Our findings question the link between speciation and morphological divergence and suggest that while plants and animals share similar modes of speciation, plants exhibit a complex spatiotemporal dynamic, challenging the typical vertebrate pattern of steadily increasing sympatry.